2017
DOI: 10.1039/c7fo00861a
|View full text |Cite
|
Sign up to set email alerts
|

A serving of blueberry (V. corymbosum) acutely improves peripheral arterial dysfunction in young smokers and non-smokers: two randomized, controlled, crossover pilot studies

Abstract: Several studies have documented the important role of polyphenol-rich foods in the modulation of vascular remodelling and function. This study aimed to evaluate the capacity of a single portion of blueberry (V. corymbosum) to acutely improve peripheral arterial dysfunction in a group of young volunteers. Twenty-four healthy males (12 non-smokers and 12 smokers) were recruited for two different randomized, controlled, crossover pilot acute studies. In the first study, non-smokers were exposed to a control treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 52 publications
(57 reference statements)
0
31
1
2
Order By: Relevance
“…This effect was associated with increased antioxidant activity of SOD1, SOD2 and GRx and reduced lipid peroxidation [66]. Blueberry consumption also decreased peripheral artery dysfunction in both smoking and non-smoking male subjects 2 h after consuming 300 g of blueberries [80]. Strawberries have shown to have beneficial effects in patients with Type II diabetes (T2D) and metabolic syndrome.…”
Section: Polyphenols In Human Healthmentioning
confidence: 99%
“…This effect was associated with increased antioxidant activity of SOD1, SOD2 and GRx and reduced lipid peroxidation [66]. Blueberry consumption also decreased peripheral artery dysfunction in both smoking and non-smoking male subjects 2 h after consuming 300 g of blueberries [80]. Strawberries have shown to have beneficial effects in patients with Type II diabetes (T2D) and metabolic syndrome.…”
Section: Polyphenols In Human Healthmentioning
confidence: 99%
“…Polyphenols in blueberry can regulate the vascular remodeling and improving the endothelial function both in smoker and in nonsmoker subjects [ 66 ]. Fermented blueberries with antihypertension properties can reduce the risk of cardiovascular diseases [ 104 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Further details about the literature search process are provided in Figure 1. Sixty-six relevant studies were identified [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88], and their results related to blood pressure are summarized in Table 1 and Table 2.…”
Section: Acns and Blood Pressurementioning
confidence: 99%
“…Del Bo et al investigated the effect of a serving of blueberry juice providing 300–350 mg ACN in restoring blood pressure after a cigarette was smoked by young otherwise healthy smokers. In one study, the SBP spike induced by smoke was restored by the blueberry juice [28], but the effect was not replicated in a following study [29].…”
Section: Acns and Blood Pressurementioning
confidence: 99%